2015
DOI: 10.1186/s11671-015-1142-6
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Analysis of Ternary and Binary Chemical Mixtures by Surface-Enhanced Raman Scattering at Trace Levels

Abstract: Surface-enhanced Raman scattering has been proven a powerful means in the fast detection and recognition of chemicals at trace levels, while quantitative analysis especially the compositional analysis of trace chemical mixtures remains a challenge. We report here a “triangle-rule” based on the principal component analysis (PCA) of surface-enhanced Raman scattering spectra, to calculate the composition of individual component of ternary chemical mixtures at trace levels, which can be simplified into the “balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…For example, Shanmukh et al demonstrated that three different respiratory syncytial virus strains were able to be differentiated by PCA using their PCA scores as shown in Figure 8A (Shanmukh et al, 2008). Recently, our group proposed a simple way to estimate compositions for binary and ternary chemical mixtures employing PCA and SERS (Hou et al, 2015a). As differences between the chemical compositions adsorbed on substrates and that in solution was neglected which is not suitable for most cases, we modified that method in order to provide a general route for the compositional analysis by considering the difference in chemicals' adsorption abilities in trace level solution (Zou et al, 2017).…”
Section: Quantitative Analysis Strategymentioning
confidence: 99%
“…For example, Shanmukh et al demonstrated that three different respiratory syncytial virus strains were able to be differentiated by PCA using their PCA scores as shown in Figure 8A (Shanmukh et al, 2008). Recently, our group proposed a simple way to estimate compositions for binary and ternary chemical mixtures employing PCA and SERS (Hou et al, 2015a). As differences between the chemical compositions adsorbed on substrates and that in solution was neglected which is not suitable for most cases, we modified that method in order to provide a general route for the compositional analysis by considering the difference in chemicals' adsorption abilities in trace level solution (Zou et al, 2017).…”
Section: Quantitative Analysis Strategymentioning
confidence: 99%
“…On the basis of evaluating the validity of the triangular rules and the equilibrium rules composed of ternary and binary mixtures of methyl orange, methylene blue, and crystal violet with different molecular structures, it was verified that the ternary and binary mixtures of the three isomers of chloroform are very similar in molecular structure. 76 They also achieved the research and development of stable and recyclable SERS substrates such as SiO 2 @Au nanorod arrays and Ag nanorods coated with Al 2 O 3 or TiO 2 film, which was applied to detect 5 µg/g polychlorinated biphenyls in soil samples. 77…”
Section: Introductionmentioning
confidence: 99%
“…treating the composition measured for chemicals adsorbed on the nanorods as the same in solution) 30 . This assumption is of course not correct for most chemical mixtures in solution, but it opens a simple and new route for quantitative analysis (specifically the compositional analysis) if we could find a way to properly consider the difference in the adsorption kinetics of chemicals in trace level solution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we performed and device a simple way to estimate the composition of chemicals adsorbed on Ag@SiO 2 nanorods as the SERS substrate by PCA (which is normally used for discriminating molecules), and prove it experimentally through several trace-level chemical mixtures in solution, by neglecting the difference in their adsorption kinetics (i.e. treating the composition measured for chemicals adsorbed on the nanorods as the same in solution) 30 . This assumption is of course not correct for most chemical mixtures in solution, but it opens a simple and new route for quantitative analysis (specifically the compositional analysis) if we could find a way to properly consider the difference in the adsorption kinetics of chemicals in trace level solution.…”
Section: Introductionmentioning
confidence: 99%